2021
DOI: 10.4103/ijd.ijd_472_21
|View full text |Cite
|
Sign up to set email alerts
|

”COVID” Terminology in Dermatology

Abstract: Ever since the beginning of COVID-19 pandemic, mucocutaneous manifestations started being noticed and are still being documented. Many of these have been described with the prefix “COVID” and may occur due to the infection (e.g., COVID rash), use of personal protective equipment in healthcare workers (e.g., COVID hand dermatitis) or extensive use of novel vaccines (e.g., COVID arm). This article attempts to summarize such entities with clinical relevance to dermatologists and physicians in general and to creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…A raised erythematous line over the distal end of the lunula is described [ 104 , 108 ]. This symptom usually occurs 2–3 weeks after the SARS-CoV infection and disappears spontaneously within 2–3 months [ 106 , 108 , 109 ]. The red crescent symptom was also reported two days after the onset of symptoms of the SARS-CoV-2 infection [ 107 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A raised erythematous line over the distal end of the lunula is described [ 104 , 108 ]. This symptom usually occurs 2–3 weeks after the SARS-CoV infection and disappears spontaneously within 2–3 months [ 106 , 108 , 109 ]. The red crescent symptom was also reported two days after the onset of symptoms of the SARS-CoV-2 infection [ 107 ].…”
Section: Introductionmentioning
confidence: 99%
“…The red crescent symptom was also reported two days after the onset of symptoms of the SARS-CoV-2 infection [ 107 ]. Most likely, this symptom occurs as a result of an immune reaction resulting from COVID-19 directed at the capillaries of the nail bed [ 105 , 106 , 109 ]. One study conducted on 55 patients indicated that the red crescent symptom occurred in 32.5% of patients (fingernails) and in 2.3% of patients (toe nails) [ 104 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation